Oil Exploration Economics: Empirical Evidence from Indonesian Geological Basins - Harry Patria; Vid Adrison (Institute for Economic and Social Research, 2015)
Oil exploration has been subject to economic research for decades. Earlier studies of exploration models are mostly discussed the behavior of exploration at the macro-level analysis such as field, firm, region, and continental. This paper then focuses on the geological and economic factors that determine the well-drilling decision at the micro-level using disaggregated panel data of 32 geological basins in Indonesia over the period of 2004–2013. This study shows that the number of drilled wells is determined significantly by the lag of success rate, lag of discovery size, lag of global oil price, and regional location of geological basin. AbstrakEksplorasi migas telah menjadi subyek ekonomi dalam beberapa dekade. Studi-studi sebelumnya dengan model eksplorasi, kebanyakan mengembangkan model Fisher (1964), secara umum dikelompokkan oleh persamaan yang menjelaskan respons eksplorasi pada tingkat makro menggunakan lapangan, perusahaan, wilayah, dan kontinental. Paper ini fokus pada analisis faktor-faktor geologi dan ekonomi yang menentukan tingkat sumur pemboran pada tingkat mikro menggunakan data panel dari 32 basin di Indonesia dalam periode 2004–2013. Hasil empiris menunjukkan bahwa tingkat sumur pemboran ditentukan secara signifikan berdasarkan tingkat keberhasilan pemboran, ukuran temuan dan harga minyak pada tahun sebelumnya serta lokasi basin geologis.Kata kunci: Pengeboran; Variabel Geologi; Variabel Ekonomi; EksplorasiJEL classifications: L71; Q35